A comparative study of the functionality and protein quality of a variety of legume and cereal flours. Issue 6 (15th October 2019) - Stone, Andrea K.; Nosworthy, Matthew G.; Chiremba, Constance; House, James D.; Nickerson, Michael T.
Abstract: Background and objectives: The functionality of legume and cereal flours is difficult to compare within the literature due to the lack of standardized methodologies and differences in processing methods. The aim of this research was to investigate the functional (pasting, water/oil holding, foaming, and emulsification) attributes and protein quality of flours derived from a wide range of cereal and legume market classes (Canada) for comparative purposes. Findings: Overall, legume flours (mean 1.77 g/g) had slightly higher oil holding capacities than cereal flours (mean 1.50 g/g), whereas their water hydration capacities were similar. In general, legume flours produced more foam with better stability than cereal flours. All legume flours had similar emulsifying properties, whereas for the cereals, oat flour had much lower emulsion stability (52.5%) than the other cereals examined (77.3%–97.7%). The in vitro protein digestibility‐corrected amino acid score (IV‐PDCAAS) of oat flour (62.46%) was much higher than that of wheat (~42%), whereas hull‐less barley (54.29%) was in between these values. Of the legumes studied, soybean and desi and kabuli chickpea flours had high protein quality (IV‐PDCAAS 72%–82%); red lentil was inferior to the aforementioned flours with an IV‐PDCAAS of 43.63%. Conclusions: Legume and cereal flours differed mostly in terms of their oil holding, foaming properties, emulsion activity and pasting properties. Selection of a cereal or legume flour will depend on the attributes desired. Significance and novelty: Information relating to various legume and cereal flour functionality and nutritional quality will enable for better ingredient selection for various food applications.